The Palaeolithic record of Warsash, Hampshire, UK: implications for late Lower and early Middle Palaeolithic occupation history of Southern Britain. Issue 5 (November 2016) - Davis, Robert J.; Hatch, Marcus; Ashton, Nick; Hosfield, Rob; Lewis, Simon G.
Abstract: This paper presents new work on the Lower and Middle Palaeolithic assemblages recovered from Pleistocene gravels of the River Test at Warsash, Hampshire. Historic map and artefact analyses enable the geological context to be established for substantial portions of the Warsash Palaeolithic record, which, when combined with new data relating to regional terrace stratigraphy and chronology, enables Warsash to be incorporated within regional and national Palaeolithic frameworks. Three key assemblages are identified: (1) a handaxe-dominated assemblage associated with gravels of the Lower Warsash Terrace that is likely to relate to hominin occupation during MIS 9; (2) a Levallois assemblage probably related to sediments overlying the Lower Warsash Terrace and likely to represent occupation in late MIS 8 and/or MIS 7; (3) a handaxe-dominated assemblage recovered from gravels of the Hamble Terrace, which is likely to have been reworked from older terrace fragments. The presence at Warsash of ficrons, cleavers and plano-convex handaxes is confirmed and their potential chronological significance considered. The Levallois record of the Solent Basin is discussed, highlighting its impoverished nature relative to the rich Levallois record of the Thames Valley. It is argued that preservation bias and/or collection history have not played a major role in creating these differences. Instead, it is likely to represent the limited dispersal of Neanderthal populations further into Britain from an entry point in the southern North Sea Basin.